An exploration of knowledge, attitudes and practices of primary health care providers providing contraceptive and family planning services in Cape Town, South Africa: a qualitative study - Fataar, Kulthum (Department of Public Health and Family Medicine, 2021)
Health care providers can play a significant role in empowering women to make informed decisions when selecting suitable contraceptive methods during contraceptive counselling. This study explores the experiences and perceptions of primary health care providers delivering contraceptives services in Cape Town to gain a deeper understanding of the delivery of contraceptive services. Ten in-depth interviews were conducted at five public primary health care facilities in urban areas in Cape Town, South Africa. Eligible participants included primary health care providers providing contraceptive services and willing to participate in the study. The qualitative software package NVivo was used to sort and manage data. Data was analysed using a thematic analysis approach. Overall, providers emphasized supporting women in contraceptive decision-making. Sexual and reproductive health training increased providers confidence to deliver appropriate contraceptive services. Furthermore, contraceptive prescribing practices were also influenced by medical eligibility criteria and women's preferred bleeding patterns. However, contraceptive prescribing practices were also influenced by providers' attitudes towards younger and older women. Challenges experienced by providers when providing contraceptive services included: contraceptive stockouts; time constraints of employed women accessing the service; and work pressure due to providing other health services. Health care providers play a critical role in facilitating women's right to accessing high quality contraceptive services. Providers in the study perceived themselves as negotiators during contraceptive counselling by considering both women's preferences and provider recommendations for contraception, whilst enabling women to make informed contraceptive decisions through provision of reproductive health information. Consequently, shifting contraceptive counselling to focus on shared decision-making may encourage autonomy during decision-making and help to limit the influence of provider attitudes on contraceptive prescribing and counselling.